Changes in blood pressure according to stature in Mexican adults - Miguel A. Perez-Sastre; Luis Ortiz-Hernandez (Universidade de São Paulo, 2021)
ABSTRACT OBJECTIVE: To determine the possible existence of differences in blood pressure change over time according to stature in Mexican adults. METHODS: We analyzed the National Household Living Standards Survey databases following household members between 2005 and 2009. We selected participants who were between 20 and 40 years old (n = 7,130). We estimated multilevel models with random intercept to analyze differences in blood pressure changes according to stature. We adjusted the models for age, locality size, geographic region, per capita family income, waist-to-height ratio, physical activity, alcohol consumption, smoking, and use of antihypertensive drugs. RESULTS: In both sexes, baseline blood pressure tended to be lower as stature decreased. The differences were maintained in both the crude and adjusted models. In men, the increases in systolic pressure over time tended to be higher as stature increased. CONCLUSIONS: Contrary to what studies observed in high-income countries, in Mexico blood pressure was positively associated with stature.